DJ-1 mutants metabolomics: finding Parkinson’s disease biomarkers - Sabala, Lúcia Isabel Paisano (2018)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder characterized by massive loss of dopaminergic neurons. Despite of decades of research the cause of sporadic PD is still unknown. PD is a complex multifactorial disorder, which probably results from an elaborate interplay of mostly unknown factors: several genes, modifying effects by susceptibility alleles, environmental exposures and gene-environment interactions, and their direct impact on the developing and aging brain. The discovery of disease-related genes has contributed substantially to the understanding of the molecular mechanisms involved in PD pathogenesis. It is known that a cascade of events leading to cell death, including the oxidative stress, contributes for the pathogenesis of PD. Among several genes mutated in familial PD, only DJ-1, an autosomal recessive gene causative of familial early onset PD, plays a direct role in oxidative defense mechanisms of substantia nigra pars compacta. The study of DJ-1 biology can provide important clues to altered cellular pathways in PD. Thus, understanding how the causative DJ-1 mutations interfere with the structure and function of DJ-1 protein is of critical importance. Mutations in DJ-1 gene may lead to loss of neuroprotective function of the protein. In this way it may occur a homeostatic imbalance in cell system and metabolites, which can be used as cellular markers of stress conditions. Therefore, the aim of this study was to compare multiple biological conditions to identify the metabolites that are significantly altered in resting and oxidative stress conditions, and access also the effect of the addition of the recombinant DJ-1 WT and mutants to SH-SY5Y cell line under normal and oxidative stress conditions. In order to achieve this goal, different recombinant protein mutants were produced and structurally characterized to access their rule in metabolite modulation. Once added to cells, an untargeted mass spectrometry analysis of metabolites was conducted in order to find potential and putative metabolites of interest. This was the first study for oxidative stress metabolomics profiling with the exogenous addition of recombinant DJ-1 WT and mutants and allowed the finding of eight possible oxidative stress biomarkers. In the future, these results must be validated in a targeted analysis, for metabolite ID verification, quantitation, functional interpretation, and pathway analysis, to try to understand their modulation by DJ-1 and their potential use as oxidative stress markers and latter as Parkinson´s disease biomarkers. Hence, these findings may contribute to future strategies for the treatment and prevention of the disease and offer new directions for recognizing disease-specific biochemical indicators.